LEGAL IMPLICATIONS OF LESSEE BANKRUPTCY ON THE STATUS OF LEASED ASSETS IN INDONESIA - Ajeng Kusuma; Emi Zulaika; Tegar Raffi Putra Jumantoro; Nur Alfi Fauziyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
In a leasing agreement, the lessee acquires the right to use the leased assets with the option to purchase them after the leasing period ends. However, when the lessee goes bankrupt, the problem that arises is regarding the position of the leasing goods in relation to other creditors, considering that all of the lessee's assets, including leased assets that are the object of leasing, can be confiscated to pay off debts. Although leasing agreements have not been regulated in detail in the law, the principles of freedom of contract and an open system contained in the Indonesian Civil Code (KUHPerdata) provide a flexible legal basis for the parties in drafting agreements that govern their rights and obligations. The results of the analysis show that in the case of bankruptcy, the goods that are the object of leasing remain the property of the lessor, although there is a risk to the lessor if the lessee is unable to continue the payments. In this case, the court-appointed receiver has the authority to decide whether the leasing agreement will be continued or terminated. If the agreement is terminated, the lessee must return the goods to the lessor, and the lessor has the right to claim compensation for the losses suffered. While leasing provides and beneficial financing solutions for the business sector, the need for clearer regulations is important to protect the rights of lessors as well as other creditors in a lessee's bankruptcy situation. This aims to minimize the risk of legal conflicts and create stronger legal certainty for all parties involved in the leasing agreement.